From Silence to muteness: Music and philosophy in the 20th century - Kraut, Jael (Amsterdam Faculteit der Geesteswetenschappen, 2010)
With the advent of new 'spiritual' music (ca. 1970-present), the return of the religious in the field of post-World War II concert music has become apparent. This return represents a break with the 19th-century tradition of absolute music and its culmination into the secular, autonomous, and formalist art of serialism of the 1950s. While the latter tended to push musico-religious issues into the background - in spite of its spiritual foundations (Goeyvaerts) - the return of spiritual music in the public sphere two decades later, indicates that the old idea (or ideal) of a sacred music has not been eradicated. But although these many new - and explicitly musico-religious - practices often make use of traditional idioms and concepts, they are not easily identifiable in terms of particular traditions and/or religious or church music. They have lived through these processes of enlightenment and secularisation, and have in many respects changed the face, and theoretical framework, of sacred music. This transformation of the sacred in the musical domain calls for a different type of analysis than traditional aesthetics, musicology and/or theology usually offer. Such an analysis has to show in which ways religious music has its place in present-day aural and musical culture, taking into account the effects of secularisation, digitalisation and interculturalism. The present project aims, first, at describing the particular ways in which practices of new music actively take part in the dynamics of the religious, of both Western and non-Western origin, within the largely secularised context of Western 'classical' music making; second, at designing and implementing theoretical strategies that open up the possibility to follow, describe, and assess the transformations of the conceptual network and (historical) practices of religious music in present-day Western musical and aural culture; and third, at enriching the debate on the limits of secularisation with a discussion of the culture of the ear - the celebrated 'sense of faith'.ABSTRACT (NL)Jael Kraut deed een filosofisch onderzoek naar muziek in de twintigste eeuw. Ze benaderde stilte als een nieuwe muzikale waarde en techniek en bestudeerde ideeën over stilte van onder anderen componisten, filosofen en schrijvers. Ze bespreekt de betekenis van stilte voor componisten als Claude Debussy, John Cage en Toru Takemitsu. Daarnaast geeft ze inzicht in het aan stilte verwante begrip verstomming, dat vooral in de tweede helft van de twintigste eeuw muziekesthetische debatten domineerde.
Keywords: Artistic research; Music philosophy and esthetics